Intersection of anxiety and negative coping among Asian American medical students - Moore, Michelle B.; Yang, David; Raines, Amanda M.; Bailey, Rahn Kennedy; Beg, Waania (Frontiers in Psychology, 2022)
Purpose Asian Americans comprise 21% of matriculating medical students in the United States but little is known about their mental health. With the growing focus on addressing the mental health of medical students, this systematic, nationwide survey assesses the relationship between anxiety and depression symptoms and coping skills among Asian American medical students. Methods A survey tool comprised of Patient Health Questionnaire-9, General Anxiety Disorder-7, and questions related to coping were emailed to members of the Asian Pacific American Medical Students Association enrolled in a USA medical school during the 2016 – 2017 academic year. We evaluated associations between anxiety and coping as well as depression and coping. Results A total of 511 Asian American medical students completed the survey. Anxiety symptoms were positively correlated with an increase in negative coping skills. Depressive symptoms were not correlated with an increase in negative coping skills. Conclusion Professionals and medical schools that aim to improve the mental health of medical students should be aware of the needs of specific populations. Asian American students who experience anxiety were more likely to utilize avoidant or negative coping strategies. In addition, Asian American students who experience depressive symptoms were not more likely to utilize these negative coping strategies. Further research must be done to evaluate the factors that influence the use of negative coping strategies to better address anxiety within the Asian American medical student population.